Factors associated with nonadherence to antiretroviral therapy in people with HIV/AIDS - Barrera-Espinoza, Richar William (2021)
Objective: To determine the association that social, clinical and therapeutic factors and coexisting diseases have with nonadherence to antiretroviral therapy in people with HIV/AIDS in 2018. Materials and methods: A cross-sectional study conducted with a sample of 117 people with HIV/AIDS on antiretroviral therapy at the Hospital Daniel Alcides Carrión. The Questionnaire for the Assessment of Adherence to Antiretroviral Therapy (CEAT-VIH)adapted for use in Peru was administered. The IBM SPSS Statistics V23 and logistic regression were used for the statistical analysis. Results: Seventeen point one zero percent (17.10 %) of the patients did not adhere to the therapy and 82.90 % adhered to their prescribed treatment. The variables most likely to predict nonadherence were sex (OR = 16.175, p value = 0.023) and HIV/AIDSrelated comorbidities (OR = 9.556, p value = 0.003). The initial viral load variable (OR = 0.152, p value = 0.030) acts as a protector because there is a greater probability of treatment adherence. Conclusions: Male sex and HIV/AIDS-related comorbidities are associated with the nonadherence to antiretroviral therapy. The initial viral load variable acts as a protector for treatment adherence.